Health planning and the problems that make its implementation difficult - Tinôco, Aldo da Fonseca (Revista de Saúde Pública, 1980)
Some problems that handicap the activity of health administrators and planners when they try to develop planned activities in public health are listed. Among such problems those regarding choice of techniques, establishment of priorities, organization and integration of services, statistical information, and policy decisions stand out.